2018
DOI: 10.14505//jarle.v8.8(30).21
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of Social Security System Legal Regulation in Kazakhstan: Experience and Standards of the OECD Members Implementation

Abstract: The main idea of the study is to substantiate legislative proposals, recommendations on the introduction in Kazakhstan of the standards of social protection systems of OECD member countries. As a result of the research, conclusions were drawn up aimed at improving the norms of the current legislation and law enforcement practice, and on modernizing measures to implement social policy in the context of the process of the progressive development of Kazakhstan as a social state. The purpose of the article is to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This means that it is also natural that the amount of people in need of social protection increases and declines. 95-98% of the knowledge about the existence accumulated until today is devoted to the problems of society, while the information that expresses human nature is even less than one percent of the sciences [3,4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This means that it is also natural that the amount of people in need of social protection increases and declines. 95-98% of the knowledge about the existence accumulated until today is devoted to the problems of society, while the information that expresses human nature is even less than one percent of the sciences [3,4].…”
Section: Resultsmentioning
confidence: 99%
“…In that period, the main issues of the state, society and democratic development were the peace of citizens, protection of the necessary resources, and raising their spirituality. According to Abu Nasr Farabi, the people of "good people city" can support each other, support each other, ease their pain, unite for a single goal and through this they can achieve what they intend to do [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, we further define the owner of the business process as the Central Administration that has the resources necessary for the implementation of the business process, who is finally responsible for the final product of the process. It is indicated that the process owner manages the process and is an integral part of the process (Khamzin et al, 2015;Buribayev et al, 2016;Apakhayev et al, 2017;Ibraev et al, 2017;Mukhamadiyeva et al, 2017a;Mukhamadiyeva et al, 2017b;Zhetpisbayev et al, 2017;Bidaishiyeva et al, 2018;Abikenov et al, 2019). Thus, we animate the subject of management, which is included in the set of activities (functions) (Khorin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%